Human beige adipocytes for drug discovery and cell therapy in metabolic diseases - Amar M. Singh (Nature Portfolio, 2020)
Methods to generate beige adipocytes from a human cell source are inefficient. Here, the authors present a protocol that efficiently generates beige adipocytes from human adipose-derived stem cells (ADSCs), which have potential utility in therapeutic development relating to metabolic diseases such as type 2 diabetes.